2016
DOI: 10.3856/vol44-issue5-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the industrial trawl fishery footprint off southeastern and southern Brazil

Abstract: ABSTRACT. This study established the spatial footprint of the industrial trawl fishing fleet operating off southeastern and southern Brazil between 2003 and 2011. It also provides estimates of the area swept by this fleet and the correspondent Utilization Index (swept area/available area) as measures of impact over the benthic ecosystem. Lastly, costs/benefits of trawling were addressed by the cumulative biomass landed during the study period expressed as a proportion of the cumulative swept area (Biomass-Swep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…Blackfin goosefish, codling and hake featured among these species as well as the pink cusk-eel (Genypterus brasiliensis) and several rays within the family Rajidae. Evidences for an increasing occupation and disturbance of slope benthic ecosystems by trawl nets have also been revealed from the offshore expansion of trawling effort between 2003 and 2011 and the total area swept by trawlers in the slope area (Port et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Blackfin goosefish, codling and hake featured among these species as well as the pink cusk-eel (Genypterus brasiliensis) and several rays within the family Rajidae. Evidences for an increasing occupation and disturbance of slope benthic ecosystems by trawl nets have also been revealed from the offshore expansion of trawling effort between 2003 and 2011 and the total area swept by trawlers in the slope area (Port et al, 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Sustainability of these catches remains uncertain, as stocks abundance has not been regularly assessed. Yet, general studies on the trawling effort dynamics and patterns of bycatch demonstrated that impacts on benthic ecosystems have increased, either through an expansion of the spatial footprint and the area disturbed by trawl nets, or by the incidental mortality impinged on nearly 30 teleost and elasmobranch species, the majority of them highly vulnerable to current fishing regimes (Port et al, 2016;Visintin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After 2007, as foreign vessels left Brazilian waters, exploitation of slope areas off southeastern and southern Brazil continued principally through the development of an ongoing trawl fishery directed at three main stocks (monkfish Lophius gastrophysus, hake Merluccius hubbsi and codling Urophycis mystacea). Because this fishery has been virtually unmanaged ever since, its impacts on these stocks as well as on the slope benthic ecosystem have become of critical concern in the context of sustainable use of resources and conservation of the deep areas of the Brazilian Exclusive Economic Zone (EEZ) (Perez et al, 2009a;Visintin, 2015;Dias & Perez, 2016, Port et al, 2016. Initiatives for managing slope trawling in Brazil date back to 2006, and were focused on the implementation of measures aiming to control the impacts of the growing national fleet and preserve productivity of the new exploited stocks.…”
Section: Introductionmentioning
confidence: 99%
“…After 2007 activities of the foreign fleet came to an end, but slope fishing persisted mostly through a bottom trawling fishing regime established by national vessels (Dias & Perez, 2016). These trawlers have gradually spread their footprint to the slope areas of southeastern and southern sectors of Brazilian coast, between 100 and 500 m depth, exploiting multiple fish and crustacean species (Port et al, 2016).…”
Section: Introductionmentioning
confidence: 99%